Antidepressant-like effects of Z-ligustilide on chronic unpredictable mild stress-induced depression in rats - Ma, Jian-Chun (Exp Ther Med, 2021)
Depression is a significant public health issue and its neuropathogenesis is associated with the dysfunction of progesterone and allopregnanolone biosynthesis. Z-ligustilide (LIG), one of the main components of the herb Angelica sinensis (Oliv.) Diels (AS), is reported to have antidepressant activities. The present study aimed to evaluate the antidepressant-like effects of LIG via behavioral tests and to measure the levels of progesterone and allopregnanolone in the prefrontal cortex and hippocampus. The results demonstrated that LIG (20 and 40 mg/kg) exerted antidepressant-like effects, confirmed by increased mobility, locomotion, rearing frequency and preference to sucrose. Furthermore, the levels of progesterone and allopregnanolone in the prefrontal cortex and hippocampus were markedly increased following treatment with LIG (20 and 40 mg/kg), indicating that both neurosteroids could serve a significant role in the antidepressant-like effects of LIG.